Physical Evidence and Quality Service Delivery in Public Hospitals in Ghana - Azila-Gbettor, Edem Max; Kwodjo Avorga, Simon Mesa; Danku, Lydia Sylvia; Atatsi, Eli Ayawo (International Review of Management and Marketing, 2013)
This study examines the value of physical environment in the delivering of quality healthcare or service in public hospitals in Ghana. Twelve set of self-administered questions were designed using Baker’s (1987) typology of servicescape. A descriptive univariate analysis was applied for the study. Based on 233 usable questionnaires retrieved from respondents, the study indicates a strong link between physical environment and quality healthcare delivery and the choice of healthcare facility. It is there by recommended that improvement in quality service delivery may be better served and improved by improving the servicescape/physical element in the services mix. Keywords: Servicescape/physical evidence; quality healthcare delivery; public hospitals; quality service JEL Classifications: L83; M1; M3